Nitrogen fixation: global perspectives. Proceedings of the 13th International Congress on Nitrogen Fixation, Hamilton, Ontario, Canada, 2-7 July 2001 - Finan, T. M.; Finan, T. M.; Layzell, D. B.; Layzell, D. B.; Newton, W.; Newton, W.; O'Brian, M. R.; O'Brian, M. R.; Vassey, J. K.; Vassey, J. K. (Wallingford :CABI Publishing, 2002)
The proceedings include the Johanna Döbereiner memorial lecture, a note on the discovery in 1965 of inorganic nitrogen complexes, the keynote address, and 68 papers in 15 sections (each mostly introduced by an overview): Chemistry and biochemistry of nitrogenase; Bacterial genomics; Plant genomics; Signal transduction; Developmental biology; Signals in the soil; Proteins in regulation and development; Stresses and factors limiting nitrogen fixation; Regulation of N2 fixation and metabolism; Nodule metabolism; Endophytic/associative plant-microbe interactions; Common themes in symbiosis and pathogenesis; Nitrification, denitrification and the nitrogen cycle; Novel applications in nitrogen fixation; and Applied aspects of nitrogen fixation. Abstracts of poster presentations, and author and subject indexes are also included.
Keywords: JJ100 - Soil Biology; ZZ394 - Biochemistry and Physiology of Microorganisms, (New March 2000); ZZ395 - Genetics and Molecular Biology of Microorganisms, (New March 2000)